Development and Characterization of a Novel Carbon-11 Labeled Positron Emission Tomography Radiotracer for Neuroimaging of Sirtuin 1 with Benzoxazine-Based Compounds - Wang Y; Liu Y; Wang Y; Bai P; Hallisey MR; Varela BL; Siewko A; Wang C; Xu Y (Dove Medical Press, 2024)
Yanli Wang,1 Yan Liu,1,2 Yongle Wang,1,3 Ping Bai,1 Madelyn Rose Hallisey,1 Breanna Lizeth Varela,1 Anne Siewko,1 Changning Wang,1 Yulong Xu1 1Athinoula A. Martinos Center for Biomedical Imaging, Department of Radiology, Massachusetts General Hospital, Harvard Medical School, Charlestown, MA, 02129, USA; 2School of Pharmacy, Lanzhou University, Lanzhou, Gansu, 730000, People's Republic of China; 3School of Pharmacy, Minzu University of China, Beijing, 100081, People's Republic of ChinaCorrespondence: Yulong Xu; Changning Wang, Email Yulong.Xu@mgh.harvard.edu; cwang15@mgh.harvard.eduIntroduction: Sirtuins (SIRTs) comprise a group of histone deacetylase enzymes crucial for regulating metabolic pathways and contributing significantly to various disease mechanisms. Sirtuin 1 (SIRT1), among the seven known mammalian homologs, is extensively investigated and understood, playing a key role in neurodegenerative disorders and cancer. This study focuses on potential as a therapeutic target for conditions such as Parkinson's disease (PD), Huntington's disease (HD), and Alzheimer's disease (AD).Methods: Utilizing positron emission tomography (PET) as a noninvasive molecular imaging modality, we aimed to expedite the validation of a promising sirtuin 1 inhibitor for clinical trials. However, the absence of a validated sirtuin 1 PET radiotracer impedes clinical translation. We present the development of [11C] 1, and 11C-labeled benzoxazine-based derivative, as a lead imaging probe. The radiosynthesis of [11C] 1 resulted in a radiochemical yield of 31 ± 4%.Results: Baseline studies demonstrated that [11C] 1 exhibited excellent blood-brain barrier (BBB) penetration capability, with uniform accumulation throughout various brain regions. Self-blocking studies revealed that introducing an unlabeled compound 1, effectively blocking sirtuin 1, led to a substantial reduction in whole-brain uptake, emphasizing the in vivo specificity of [11C] 1 for sirtuin 1.Discussion: The development of [11C] 1 provides a valuable tool for noninvasive imaging investigations in rodent models with aberrant sirtuin 1 expression. This novel radiotracer holds promise for advancing our understanding of sirtuin 1's role in disease mechanisms and may facilitate the validation of sirtuin 1 inhibitors in clinical trials.Keywords: sirtuin 1, neuroimaging, benzoxazine-based derivative, blood-brain barrier